Analysis of Influence Leadership and Professionalism on Teacher Performance in Yayasan Pendidikan dan Pembinaan Umat Al-Fath - Yudi Rahman; Hosni Suradji (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
This study aims to examine the influence of leadership and professionalism on teacher performance in Yayasan Pendidikan dan Pembinaan umat Al-Fath Kabupaten Bogor. The subject of this study was a teacher in Yayasan Pendidikan dan Pembinaan Umat Al-Fath Kabupaten Bogor, totaling 44 teachers. Data was collected using questionnaires, from 44 questionnaires distributed, returned 44 questionnaires and 44 questionnaires that could be evaluated. The tool used in this study is multiple linear regression with the help of SPSS (Statistical Pakage for Social Scienci) software version 22.0. This study produced 2 findings in accordance with the proposed hypothesis. First, leadership influences performance. Both found the influence of professionalism on performance.